Innovations and continuous improvements and their impact on firm's performance. - Mohamed, Mohd Zain; M. Kassim, Norizan (IGI Global, 2010)
This paper examines the influence of innovation and continuous improvement practices on the competitiveness of firms, which in turn affect their performance. Results obtained from 112 Qatari firms confirm that continuous improvements had a significant positive influence on the firms’ competitiveness. Among six of the ten Ekvall’s creative climate factors examined, only four had some positive influence on the competitiveness of the firms. The authors also found that the organization’s internal environment had significant positive influence on the competitiveness of the firms. Furthermore, results show that organizational competitiveness significantly influenced performance. Managerial implications of the findings are also provided.